?RESEARCHES ON CHEMICAL, MINERALOGICAL AND BACTERIAL ANALYSIS OF BHOLARI SAND (Biological Sciences - PJSIR, 1995)
Bholari is a small village situated near Kotri, in province Sindh of Pakistan. It contains huge deposits of Si02 sand which are extensively utilized in sand moulding, both for ferrous and non-ferrous castings (specially at T & T Foundry, Kotri). Earlier no proper work is carried out on moulding properties of Bholari sands. Authors have col- lected the samples from the site and have studied the moulding properties, analysis and bacterial hazards. both alone and mixture with molasses, a common binder of moulding sands. It is concluded that although this sand can not be recommended as natural bonded sand because it contains very little amount of clay « 0.5%) but it can be used as moulding material after addition of 5-8% clay, 1.5% water and an adequate quantity of additives e.g. molasses. The bacteria -culture investigation carried out at Veterinary Research Institute, Lahore shows no growth in the sand and its mixture with molasses, hence, the foundrymen working with this sand remain free pollution created by gases and Si02 dust evolved during moulding, from any bacterial hazard.